Conocimiento del idioma inglés y el desenvolvimiento profesional de los graduados de hotelería y turismo del año 2014 al 2018 - Aviles Varas, Maruska Geraldine (2019)
The present research work is focuses analyze the importance to the knowledge of the English language to improve the professional development in the graduates of Hospitality and Tourism Career, there are diverse factors that prevent the adequate learning of the foreign language in the students of the tourist sector, due to the fundamental that becomes the language in the area, it is considered an issue of importance for all the university community. Questions were developed to survey graduates and students of the career, also interviewed teachers of the subject of English to identify possible solutions to the problem posed. Based on the results, a proposal was obtained directed to the process of international academic mobility for the learning of the English language for teachers and students, where the steps to follow to access programs that strengthen the skills in the area of English in an American country are contemplated to stimulate the practice of the Anglo-Saxon language